1991
DOI: 10.1007/bf01955005
|View full text |Cite
|
Sign up to set email alerts
|

Cord serum IgE and early detection of the atopic phenotype: Suitable for routine screening?

Abstract: Cord serum IgE has been shown to be a valuable marker for the prediction of atopy. Our study was designed to verify these findings for possible systematic screening recommendation. Our study consisted of 338 children who were followed from birth to 18 months. Cord serum IgE was measured by paper immunosorbent test and radioimmunoassay. All other data (sex, family history and environment, diet, occurrence of atopic manifestations) were recorded. Of the 338 children, 118 (34.9%) developed obvious clinical sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Furthermore, this study supports previous reports suggesting that the determination of tIgE from cord blood or during the first years of life may not be helpful for the diagnosis or prediction of atopy [20][21][22].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, this study supports previous reports suggesting that the determination of tIgE from cord blood or during the first years of life may not be helpful for the diagnosis or prediction of atopy [20][21][22].…”
Section: Discussionsupporting
confidence: 88%
“…Although there is no agreement on the threshold level that is associated with increased risk of clinical atopic disorders, several studies have found that cord blood IgE levels between 0.9 and 1.3 IU/mL are associated with significantly increased risk particularly in relation to early sensitization in later childhood. 38,45 Indeed, cord blood IgE levels in general are a weaker predictor of later atopic risk unless the more extreme levels are considered. Use of lower cutoff values in prior research 46 results in significant changes in the sensitivity, specificity, and positive predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity of cord blood IgE was quite low at 8.5-33% [21][22][23] . A family history of atopic disease or maternal total IgE levels was more sensitive than the level of cord blood IgE to detect children at risk of atopy [22,40] .…”
Section: Discussionmentioning
confidence: 99%
“…Cord blood immunoglobulin E (IgE) has received much attention over the years. However, because of its low sensitivity, it is not a reliable predictive marker of atopic diseases [21][22][23] . Various soluble cytokines and cytokine receptors in cord blood, such as sCD30, sCD23 and the IL-4 receptor, have also been studied, but none has been found to be a significant predictive factor for atopic disorders [24,25] .…”
Section: Introductionmentioning
confidence: 99%